Women Travellers, Romantic-era science and the Banksian empire. (1st May 2019) - Thompson, Carl
Abstract : This article explores the contributions to science made by three women travellers in the Romantic period: Maria Riddell (1772–1808), who visited the Caribbean between 1788 and 1791; Maria Graham (later Callcott, 1785–1842), who visited South America between 1821 and 1825; and Sarah Bowdich (later Lee, 1791–1856), who visited Madeira and West Africa in the late 1810s and early 1820s. As well as mapping their scientific accomplishments, the article explores their integration into contemporary scientific networks and circuits of knowledge production, paying particular attention to their connections with the so-called 'Banksian empire' of Sir Joseph Banks (1743–1820). Simultaneously, it addresses the diverse strategies adopted by Riddell, Graham and Bowdich as they sought to negotiate the constraints undoubtedly faced in this period by women seeking to participate in scientific endeavours; however, the article also argues that such constraints did not ultimately prevent Riddell, Graham and Bowdich from attaining scientific authority and influence, both within the contemporary scientific community and with the wider public.